Rancangan Buku Saku Serangga Polinator Sebagai Penunjang Pembelajaran Biologi di Bakal Sekolah Alam Kampung Wisata Isyo Hils Rhepang Muaif Nimbokrang, Jayapua - Ramandey, Euniche R.P.F.; Warikar , Evie Lilly (Bakti Hayati: Jurnal Pengabdian Indonesia, 2023)
Abstract    The learning media for the identification of pollinator insects is deemed necessary to be distributed through socialization and practice for elementary school children, and teachers at the “Isyo Hills” Nature School in Kampung Rhepang Muaif. Directly arouse interest and enthusiasm for learning for elementary school children at the Nature School "Isyo Hills" about science material, especially learning to recognize insects in nature. From this spirit, the character of love and care for the preservation of the heart in Papua will grow. The objectives of the implementation of this community service activity are: To design learning media in the form of insect identification pocket books for elementary school children and to introduce and practice directly introducing insects through insect identification books to teachers, elementary school children, and school management groups. Nature "Isyo Hills" in Kampung Rhepang Muaif, Nimbokrang, Jayapura-Papua. The method used in designing this book begins with the stage of making the concept of the material, making the design and character selection to the layout, and finishing the final result. This design resulted in a booklet featuring a discussion of the introduction of butterfly insects. The next activity is the implementation of training which is carried out for 1 day, namely on August 27, 2022, involving 16 participants from the "Isyo Hills" Nature School students from representatives of elementary school grades 1–5 and junior high school students. The training provided includes the introduction of insects, then the children practice directly identifying butterflies in nature. This service activity was carried out for teaching staff and elementary school children at the "Isyo Hills" Natural School in Rhepang Muaif Village. The enthusiasm of the participants in participating in this training activity was very high. This indicates that the service participants positively welcomed the activities that had been carried out.